Akselerasi Pelayanan Nasabah Melalui Transformasi Digital Byond dan Peningkatan Efisiensi Administrasi di BSI KCP Palangkaraya 1 - Pusvita Ardian Dinata; Rita Sarlawa; Ellsa Riyany; Khusnul Khotimah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This community service study aims to analyze the acceleration of customer service through digital transformation using the BYOND application and to evaluate the improvement of administrative efficiency at BSI KCP Palangkaraya 1. The method employed is descriptive qualitative, with data collection techniques including observation, interviews, and documentation conducted from February to March 2026. The results indicate that conventional service processes at Customer Service and Teller units are still dominated by physical forms and manual verification, leading to long queues. The implementation of the BYOND application faces technical obstacles such as facial verification (liveness detection) failures and low digital literacy among senior customers. However, through direct education and mentoring programs, there has been a significant increase in administrative efficiency, a reduction in physical queues, and improved accountability of transaction data. This study confirms that the integration of digital technology, accompanied by intensive mentoring, can create a more responsive and efficient sharia banking ecosystem in Palangka Raya.